2013
DOI: 10.1111/1469-0691.12150
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of extended-spectrum β-lactamase-producing Enterobacteriaceae in humans living in municipalities with high and low broiler density

Abstract: Prevalence of, and risk factors for, carriage of extended-spectrum β-lactamase (ESBL) -producing Enterobacteriaceae were determined for 1025 Dutch adults in municipalities with either high or low broiler densities. Overall prevalence of ESBL carriage was 5.1%. The hypothesis that individuals in areas with high broiler densities are at greater risk for ESBL carriage was rejected, as the risk was lower (OR = 0.45; p 0.009) for these individuals. Owning a horse increased the risk (OR = 4.69; p ≤0.0001), but horse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 18 publications
7
65
0
1
Order By: Relevance
“…The findings of Reuland et al showing that the use of PPIs is a risk factor were confirmed [7]. In the present study, previous use of antibiotics and close contact with horses were not confirmed as being risk factors, although these determinants have been identified as risk factors in other studies [5,30].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The findings of Reuland et al showing that the use of PPIs is a risk factor were confirmed [7]. In the present study, previous use of antibiotics and close contact with horses were not confirmed as being risk factors, although these determinants have been identified as risk factors in other studies [5,30].…”
Section: Discussionsupporting
confidence: 66%
“…An increased environmental exposure due to livestock did not cause a higher prevalence of carriage of ESBL/pAmpC-E in the population: the prevalence of 4.5% (95% CI 3.7e5.4) is comparable to the prevalence previously reported in the general population living in areas with high-as well as low-broiler densities [5], but lower than the prevalence observed among the general population in Amsterdam, although this urban population had a higher travel frequency, which may explain the difference [7]. The most common ESBL genes detected were bla CTX-M-15 , bla CTX-M-14/17 and bla CTX-M-1 , which is in accordance with other recent population-based studies in the Netherlands [7,24].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…[26][27][28][29] The increasing o pathogenic and commensal ESBL-producing E. coli strains are originated from different sources (such as human, food, and animal) and the dissemination of antibiotic resistance among other members of Enterobacteriaceae is a worldwide problem in the control and treatment of infections in human and animals. 20,[30][31][32][33][34] Moreover, some studies have shown that infections caused by ESBL-producing bacteria leads to the increase in the economic costs of infections treatment and the morbidity and mortality of diseases. 35 Furthermore, resistance to other antibiotic classes was observed in ESBL-producing E. coli more than non-ESBL-producing iso lates.…”
Section: Discussionmentioning
confidence: 99%